2021
DOI: 10.5194/isprs-annals-v-2-2021-113-2021
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Platform for Management and Visualization of Geometric Documentation Products of Cultural Heritage Sites

Abstract: Abstract. The mission of digital Cultural Heritage (CH) repositories goes beyond engagement and dissemination; their research data should be approached and correlated spatially and semantically in the service of conservation and accessibility. Therefore, a flexible system is needed to expand, reuse and repurpose their content, addressing online collaboration, real time progress and ease of use. Towards this direction, the “METEORA” web-based platform is a novel and holistic approach to the organization, manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The input data are the following four models: (i) Middlebury TempleRing [ 52 ]; (ii) the Human of CoRBS dataset [ 53 ]; (iii) the Anton Memorial of Harvest4D consortium [ 54 ]; and (iv) the Meteora site by the Meteora Project [ 48 ]. Table 1 shows the format, size and geometric attributes of the 3D models used as AR overlays, before and after their conversion into multi-resolution structures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The input data are the following four models: (i) Middlebury TempleRing [ 52 ]; (ii) the Human of CoRBS dataset [ 53 ]; (iii) the Anton Memorial of Harvest4D consortium [ 54 ]; and (iv) the Meteora site by the Meteora Project [ 48 ]. Table 1 shows the format, size and geometric attributes of the 3D models used as AR overlays, before and after their conversion into multi-resolution structures.…”
Section: Methodsmentioning
confidence: 99%
“…It extends the capabilities of existing frameworks such as AR.js and Three.js, integrating them seamlessly to handle a multi-resolution 3D format and enable user-friendly interactions and parameter adjustments in real time. The choice of AR.js is made because the underlying AR library accounts for its compatibility across browsers and devices with WebGL and WebRTC features [ 46 ], while the selection of the Nexus.js algorithm lies in its proven capability to handle arbitrary geometry [ 47 , 48 ], its good compression ratio and its fast decoding (3 M triangles per second with normal and colors in a single thread) even at low-end devices. By comparing some of the aforementioned notable rendering schemes and their respective advantages and limitations with the proposed one, it is shown that the suggested method achieves progressive streaming and the responsive view-dependent visualization of textured high-resolution 3D models of a large size (more than 1 GB) and data volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CMS has an easy-to use and responsive Graphical User Interface (GUI) that comprises various 3D and 2D viewports for real-time data preview, along with buttons, lists and other types of inputs for mapping the described operations (Ioannidis et al, 2021). When the admin logins and uploads a 3D file, the list of the available models for editing is updated (Figure 5).…”
Section: Content Management Systemmentioning
confidence: 99%
“…3D digitization is otherwise important to foster accessibility and inclusiveness; in fact, through this process, it is possible to provide virtual access to resources currently inaccessible and offer a support for people with disabilities who visit cultural sites (Scianna and Di Filippo, 2019;Hallot et al, 2021;Agnello et al, 2022). Furthermore, although it cannot prevent risks and deteriorations, it can contribute to the protection of some historical objects (avoiding their direct manipulation) and provides a useful database for heritage monitoring (Nishanbaev, 2020;Ioannidis et al, 2021;Bruno et al, 2022). The great attention to cultural heritage digitization by the scientific community inevitably has led to improvements in technology and methodology.…”
Section: Introductionmentioning
confidence: 99%